Harnessing long-range surface plasmon excited by fluorescent molecules near an ultrathin gold film - Liping Fang; Jinlong Peng; Xin Lin; Vladimir Zaitsev; Irina Kamenskikh; Rui Chen (Journal of Experimental Nanoscience, 2025)
Harnessing the fluorescent properties of molecules is attractive for applications, such as versatile quantum light source based on organic molecules. Ultrathin gold films, which can support long-range surface plasmons (LRSP), offer enormous potential to tune the emitting properties of fluorescent molecules. We studied the fluorescent properties of a sub-monolayer of molecules near the surface of a LRSP-supportable monolithic chip fabricated on a silicon wafer pre-deposited with a 30-nm-thick gold film. The molecule-gold distance was finely tuned to investigate the near-field interactions between the molecules and the resonant optical modes in the silicon chip. Significant modifications of the fluorescent properties were observed for molecule-gold distance up to 100 nm. The propagation length of the LRSP mode exhibits 25-fold enhancement over that for the short-range surface plasmon, which potentially allows improved flexibility and compactness for on-chip integration. An analytical model was developed to predict the fluorescent properties (lifetime and emission spectra) by treating the fluorescent molecules as dipole emitters. Our experiments, in excellent agreement with the analytical model, potentially pave the way for the design and manufacture of future on-chip quantum light source and bionanotechnolgy platforms with tailored spectroscopic requirements.